A safe technique of anterior column lag screw fixation in acetabular fractures - Sen, Ramesh Kumar (Springer-Verlag, 2012)
PURPOSE: Conventional anterior column lag screw fixation in acetabular fracture is a difficult technique that has potential risks of vascular injury, hip joint penetration and excessive radiation exposure. We propose a safe technique of anterior column lag screw fixation (in-out-in technique) and present the outcome. MATERIALS AND METHODS: Twenty-seven acetabular fractures were operated through an iliofemoral approach, where the ‘in-out-in technique’ of lag screw fixation was a part of the surgical procedure. The technique involved insertion of a malleolar screw (4.5 mm) or 6.5 mm partially threaded cancellous screw from the outer side of the iliac wing, 0.5–1 cm posterior and inferior to the anteroinferior iliac spine. The screw comes out of the bone surface to re-enter into the anterior part of iliopectineal eminence, and finally gains purchase in the lateral part of superior pubic ramus. The screw fixation procedure was under direct visualization without resorting to an image intensifier. The average follow-up of the patients was at 18.6 months (range 12–36 months). RESULTS: No loss of reduction, joint penetration or visceral and neurovascular injury were documented. The average duration of surgery was 70 min and blood loss was 290 ml. All fractures were united after an average period of 2.8 months. Excellent to good functional outcome was observed in 24 patients (88 %), on evaluation with Merle D’Aubigne and Postel score at the latest follow-up. CONCLUSION: We conclude that the ‘in-out-in technique’ is a safe and effective method of anterior column lag screw fixation in acetabular fractures. It provides rigid stability and minimizes surgical duration, radiation exposure and intra-operative complications.